Lost Opportunities: Work during High School, Establishment Closures and the Impact on Career Prospects - Dagmar Müller (Research Institute of Industrial Economics (IFN), 2021)
Relying on Swedish linked employer-employee data over a 30-year period, I study the importance of work during high school for graduates' school-to-work transition and labor market outcomes. I show that employer links established through work during school provide students with an important job-search channel, accounting for 30 percent of direct transitions into regular employment. I use the fact that some graduates are deprived of this channel due to establishment closures just prior to graduation and labor market entry. I compare classmates from the same vocational high school tracks to identify the effects of the closures and show that the closure of a previous in-school establishment leads to an immediate and sizable negative effect on employment after graduation. The lost employer connections have also persistent, but diminishing negative effects on employment and earnings for up to 10 years. Parts of the negative effect are driven by the loss of employers links that offer job opportunities in industries related to graduates' specialization in vocational school. I find evidence supporting that students who lose such relevant links shift towards jobs in less- relevant industries.
Keywords: J01; J64; 330; Social contacts; Young workers; Labor market entry; Establishment closures